PENGARUH PENCAMPURAN MINYAK NABATI TERHADAP AKTIVITAS ANTIBAKTERI DAN OTENTIKASI MINYAK ATSIRI JAHE GAJAH DENGAN SPEKTROSKOPI FTIR DAN KEMOMETRIK - Suryati Syafri; Dhiya Ulwafi; Assyifa Nurul Sabilla; Dachriyanus Hamidi; Syofyan Syofyan (Sekolah Tinggi Ilmu Kesehatan Samarinda, 2026)
Big ginger essential oil (BGEO) is a natural source with antibacterial activity. Some traders on online shopping platforms sell ginger oil that may be diluted with a solvent, which could harm customers by increasing the risk of allergies and reducing its biological activity. This study aimed to determine the effect of diluting BGEO with vegetable oils on antibacterial activity and to authenticate BGEO purchased from an online market using FTIR spectroscopy combined with chemometrics. Pure BGEO was obtained by hydrodistillation. Ten BGEO products were obtained from an online shopping platform. The pure BGEO was diluted with three vegetable oils: soybean oil (SO), virgin coconut oil (VCO), and palm oil (PO). Antibacterial activity was evaluated using the microdilution method. The result showed the Minimum Inhibitory Concentration (MIC) values of pure BGEO against Staphylococcus aureus ATCC 25923 and Escherichia coli ATCC 25922 were 6.25 mg/mL and 12.50 mg/mL, respectively. The dilution of big ginger essential oil with vegetable oil did not reduce its antibacterial activity. The adulteration of BGEO with palm oil enhanced its antibacterial activity against Gram-positive and Gram-negative bacteria. Most commercial big ginger oils were not similar to BGEO from West Sumatra, and one of the commercial ginger oils may contain vegetable oil as a diluent. Principal Component Analysis (PCA) successfully classified pure BGEO and commercial BGEO. Adulteration of big ginger essential oil with vegetable oil did not reduce its antibacterial activity.